Estrogen Deficiency Induces Mitochondrial Damage Prior to Emergence of Cognitive Deficits in a Postmenopausal Mouse Model - Zhao, Wei; Hou, Yue; Song, Xinxin; Wang, Lei; Zhang, Fangfang; Zhang, Hanting; Yu, Haiyang; Zhou, Yanmeng (Frontiers in Aging Neuroscience, 2021)
Background: Estrogen deficiency contributes to the development of Alzheimer’s disease in menopausal women. In the current study, we examined the impact of estrogen deficiency on mitochondrial function and cognition using a postmenopausal mouse model. Methods: Bilateral ovariectomy was conducted in adult female C57BL/6J. Cognitive function was examined using the Morris water maze test at 2 weeks, 1, 2, and 3 months after ovariectomy. Neurodegeneration was assessed using an immunofluorescence assay of MAP2 in the hippocampus and immunoblotting against PSD95. Mitochondrial function in the hippocampus was assessed using immunoblotting for NDUFB8, SDHB, UQCRC2, MTCO1, and ATP5A1. Mitochondrial biogenesis was examined using immunoblotting for PGC-1α, NRF1, and mtTFA. Mitochondrion fission was assessed with immunoblotting for Drp1, whereas mitochondrion fusion was analyzed with immunoblotting for OPA1 and Mfn2. Mitophagy was examined with immunoblotting for PINK1 and LC3B. Mice receiving sham surgery were used as controls. Results: Ovariectomy resulted in significant learning and memory deficits in the Morris water maze test at 3 months, but not at any earlier time points. At two weeks after ovariectomy, levels of Drp1 phosphorylated at Ser637 decreased in the hippocampus. At one month after ovariectomy, hippocampal levels of NDUFB8, SDHB, PGC-1α, mtTFA, OPA1, and Mfn2 were significantly reduced. At two months after ovariectomy, hippocampal levels of MAP2, PSD95, MTCO1, NRF1, and Pink1 were also reduced. At three months, levels of LC3B-II were reduced. Conclusions: The cognitive decline associated with estrogen deficiency is preceded by mitochondrial dysfunction, abnormal mitochondrial biogenesis, irregular mitochondrial dynamics, and decreased mitophagy. Thus, mitochondrial damage may contribute to cognitive impairment associated with estrogen deficiency.